Superior in vivo Wound-Healing Activity of Mycosynthesized Silver Nanogel on Different Wound Models in Rat - Gaikwad, Swapnil; Birla, Sonal; Ingle, Avinash P.; Gade, Aniket; Ingle, Pramod; Golińska, Patrycja; Rai, Mahendra (Frontiers in Microbiology, 2022)
Wound healing is a complex phenomenon particularly owing to the rise in antimicrobial resistance. This has attracted the attention of the scientific community to search for new alternative solutions. Among these, silver being antimicrobial has been used since ancient times. Considering this fact, the main goal of our study was to evaluate the wound healing ability of mycofabricated silver nanoparticles (AgNPs). We have focused on the formulation of silver nanogel for the management of wounds in albino Wistar rats. Mycosynthesized silver nanoparticles from Fusarium oxysporum were used for the development of novel wound healing antimicrobial silver nano-gel with different concentrations of silver nanoparticles i.e. 0.1, 0.5, and 1 mg g-1. The formulated silver nano-gel demonstrated excellent wound healing activity in the incision, excision, and burn wound healing model. In the incision wound healing model, silver nano-gel of concentration 0.5 mg g-1 exhibited superior wound healing effect, whereas in the case of excision and burn wound healing model, silver nano-gel of concentrations 0.1 and 1 mg g-1 showed enhanced wound healing effect, respectively. Moreover, silver nano-gel competently arrests the bacterial growth on the wound surface and offers an improved local environment for scald wound healing. Histological studies of healed tissues and organs of the rat stated that silver nanoparticles in less concentration (1 mg g-1) do not show any toxic or adverse effect on the body and promote wound healing of animal tissue. Based on these studies, we conclude that the silver nanogel prepared from mycosynthesized silver nanoparticles can be used as a promising antimicrobial wound dressing.